INFILTRASI DAN SIMPANAN AIR PADA JENIS NAUNGAN YANG BERBEDA DI LAHAN KOPI DESA AMADANOM KECAMATAN DAMPIT KABUPATEN MALANG - Ika Lestiana Sari; Sugeng Prijono (Jurnal Tanah dan Sumberdaya Lahan, 2019)
Coffee plants belong to important commodities in Indonesia. In 2003, coffee productivity in Indonesia reached 725 kg ha-1 and decreased 0.41% in 2016 to 722 kg ha-1. Climate change is expected on the production of coffee crops. Some possibilities to reduce the effect of climate change are mitigation by implementing shade plants. This study aimed to understand the influence of differences shade on coffee plants toward infiltration and water storage in the soil. This study used a randomized block design that consisted of three treatments and five replications. The parameters observed were infiltration and water content in the soil conducted in three periods as well as the bulk density, particle density, porosity, macro pore, texture and structure. The results showed that the differences of shade on coffee plants gave a significant effect (p<0.5) toward infiltration of water. The highest total of infiltration was found in coffee plant with sengon shade (309.968 ± 5.855 mm) from total rainfall of 354.731 mm. The results of water storage observation showed that the differences of shade in coffee plants had no significant effect (p>0.05) toward the amount of water storage in the soil. The value of water storage in the soil continued to decrease. The highest value in the coffee plant with durian shade was (287.0 ± 15.086 mm) in the first week and the lowest value was found in the coffee plant with sengon shade (239.4 ± 10.871 mm) in fifth week.